Bootstrap Liberalism : Texas Political Culture in the Age of FDR - Cunningham, Sean P. (Book collections on Project MUSE., 2022)
"The Lone Star State is often viewed as a bastion of conservative politics and rugged "bootstrap" individualism, but that narrative overlooks the fact that FDR's New Deal liberalism was quite popular in Texas, much more so than previous histories of the era have suggested. While it is true that many Texas Democrats remained staunchly conservative during Franklin Roosevelt's presidency, and is also true that many of these conservatives formed the basis of an established majority that would grow stronger in the decades that followed, it is simultaneously true that ordinary voters-and a good many politicians-embraced New Deal policies, federal experimentation, and direct economic aid, and often did so enthusiastically. Texas political leaders recognized the popularity of the New Deal and identified themselves with FDR for their own political advantage. Using original resources mined from six research archives, Bootstrap Liberalism explores various policy debates as they unfolded at the local, state, and national levels throughout the Great Depression and World War II eras, revealing a consistent brand of pro-New Deal messaging that won favor with voters across the state"--